Serum miR‐221 serves as a biomarker for Parkinson's disease. (October 2016) - Ma, Wenbin; Li, Yingying; Wang, Chao; Xu, Fan; Wang, Meiling; Liu, Yiming
Abstract : Parkinson's disease (PD) is the common age‐related neurodegenerative disorder. Sensitive, noninvasive biomarkers that facilitate PD diagnosis and stage assignment are currently unavailable. This study aims to investigate the potential of 16 previous reported PD‐associated miRNAs as novel biomarkers for PD. The expression of 16 serum miRNAs was measured by quantitative reverse transcriptase polymerase chain reaction in 138 PD patients and 112 control populations. Analyses were undertaken to assess the specificity and sensitivity of miRNAs to predict PD. In addition, the relationship between deregulated miRNAs and Part III of the United Parkinson's Disease Rating Scale (UPDRS‐III) and Part V of the UPDRS (UPDRS‐V; the modified Hoehn and Yahr staging of PD) in PD patients was also assessed. It was found that the serums miR‐29c, miR‐146a, miR‐214, and miR‐221 were significantly decreased in PD patients compared with healthy control populations. In addition, serum miR‐221 was positively correlated with UPDRS‐III ( r = .4702) and UPDRS‐V ( r = .4788) score in PD patients. Furthermore, the receiver operating characteristic result of serum miR‐221 for prediction of PD was 0.787. Our preliminary findings indicate that downregulated serum miR‐221 might be a potential biomarker for PD evaluation.